2010
DOI: 10.1161/strokeaha.109.571844
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Study of ABCD 2 Score, Carotid Stenosis, and Atrial Fibrillation for Early Stroke Prediction After Transient Ischemic Attack

Abstract: Background and Purpose-Transient ischemic attack (TIA) etiologic data and the ABCD 2 score may improve early stroke risk prediction, but studies are required in population-based cohorts. We investigated the external validity of the ABCD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
128
3
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(141 citation statements)
references
References 34 publications
6
128
3
4
Order By: Relevance
“…Incidence of stroke in the high-risk group is 2-8 times higher than that of the low-risk and moderate group; incidence of secondary stroke in low-risk, moderate-risk and high-risk groups reached 3.1%, 9.8%, 17.8%, respectively, within 90 d. incidence of secondary stroke in medium and high-risk groups accounting for about 90%, are higher than that of the low-risk group. 2,14,15 Other studies demonstrated that TIA patients in low-risk (0-3 points), moderate-risk (4-5 points), high-risk groups (6-7 points) presented incidence of cerebral infarction of 3%, 31% and 3%, respectively (P<0.05) within 7 d. TIA patients with secondary to cerebral infarction within 7 d probability and linear correlation between ABCD2 score showed that high score indicates high incidence of cerebral infarction; ABCD2 score >6 displays highest incidence in patients, and risk of recurrence of cerebral infarction is seven times higher than that of other patients. 16,17 To date, numerous studies proved that efficiency of ABCD2 score for early prediction of cerebral infarction after TIA value is higher than that of ABCD score method, with recommendations of AHA/ASA for clinical evaluation of the prognosis of patients with TIA risk method.…”
Section: Abcd2 Scorementioning
confidence: 99%
See 4 more Smart Citations
“…Incidence of stroke in the high-risk group is 2-8 times higher than that of the low-risk and moderate group; incidence of secondary stroke in low-risk, moderate-risk and high-risk groups reached 3.1%, 9.8%, 17.8%, respectively, within 90 d. incidence of secondary stroke in medium and high-risk groups accounting for about 90%, are higher than that of the low-risk group. 2,14,15 Other studies demonstrated that TIA patients in low-risk (0-3 points), moderate-risk (4-5 points), high-risk groups (6-7 points) presented incidence of cerebral infarction of 3%, 31% and 3%, respectively (P<0.05) within 7 d. TIA patients with secondary to cerebral infarction within 7 d probability and linear correlation between ABCD2 score showed that high score indicates high incidence of cerebral infarction; ABCD2 score >6 displays highest incidence in patients, and risk of recurrence of cerebral infarction is seven times higher than that of other patients. 16,17 To date, numerous studies proved that efficiency of ABCD2 score for early prediction of cerebral infarction after TIA value is higher than that of ABCD score method, with recommendations of AHA/ASA for clinical evaluation of the prognosis of patients with TIA risk method.…”
Section: Abcd2 Scorementioning
confidence: 99%
“…2 In recent years, a growing number of studies have shown that ABCD2 score for prediction of stroke after TIA features more limitations because of lack of etiology assessment, making ABCD2 score prediction value questionable. 2,15,17 …”
Section: Abcd2 Scorementioning
confidence: 99%
See 3 more Smart Citations